2002
DOI: 10.1152/ajpgi.00326.2001
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+sparks and BK currents in gallbladder myocytes: role in CCK-induced response

Abstract: Pozo, María J., Guillermo J. Pé rez, Mark T. Nelson, and Gary M. Mawe. Ca 2ϩ sparks and BK currents in gallbladder myocytes: role in CCK-induced response. Am J Physiol Gastrointest Liver Physiol 282: G165-G174, 2002. First published October 24, 2001 10.1152/ajpgi.00326. 2002We sought to elucidate the regulation of gallbladder smooth muscle (GBSM) excitability by localized Ca 2ϩ release events (sparks) and large-conductance Ca 2ϩ -dependent (BK) channels by determining whether sparks exist in GBSM and, if so,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…Ca 2ϩ -activated K ϩ channels are present in GBSM and are involved with reducing excitability through a hyperpolarization (28,34,54), which may explain the tendency for plasma membrane hyperpolarization observed in some GBSM immediately after the application of CCCP. It is also possible that CCCP and FCCP reduced APs and Ca 2ϩ flashes through transient activation of other types of potassium channels known to exist in GBSM (17,31,34,54).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ca 2ϩ -activated K ϩ channels are present in GBSM and are involved with reducing excitability through a hyperpolarization (28,34,54), which may explain the tendency for plasma membrane hyperpolarization observed in some GBSM immediately after the application of CCCP. It is also possible that CCCP and FCCP reduced APs and Ca 2ϩ flashes through transient activation of other types of potassium channels known to exist in GBSM (17,31,34,54).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have previously demonstrated that VDCC and nonselective cation channels in the plasma membrane (27,30,33,54) and the SR (2,3,27,34) are also essential for rhythmic activity in the GBSM. Collectively, these findings indicate that the mitochondrion, SR, and plasma membrane channels constitute key components of the GBSM pacemaker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallbladder smooth muscle cells were dissociated enzymatically using a previously described method (Pozo et al, 2002). In brief, the gallbladder was cut into small pieces and incubated for 34 min at 37°C in enzyme solution (for composition see Solutions and Drugs) supplemented with 1 mg/ml bovine serum albumin (BSA), 1 mg/ml papain, and 1 mg/ml 1,4-dithio-DL-threitol.…”
Section: Methodsmentioning
confidence: 99%
“…191 Furthermore, a similar coupling mechanism between Ca 2+ sparks and BK channel activity was demonstrated in gallbladder myocytes. 192 Thus, inhibition and/or downregulation of BK channels could be the cause of smooth muscle cell contractility alteration, as found in urinary bladder overactivity. 193 In brief, despite tissue and interspecies diversity, a general behavior can be observed as a common factor for BK contribution to cell physiology.…”
Section: Bk Channels In Smooth Musclesmentioning
confidence: 99%